Menstrual Hygiene Management Practice in Magelang Senior High School - Tuti Sukini; Sri Widatiningsih; Siti Rofiah (Midwifery and Nursing Research, 2021)
Background: Menstrual Hygiene Management is the management of hygiene and health when women experience menstruation. UNICEF research results state that 46% of young women in Indonesia change sanitary napkins less than 2 times a day, whereas in theory changing sanitary napkins is at least 3-4 hours a day. Use for more than 8 hours causes genital irritation and itching which will have an impact on health. The purpose of this study was to determine the practice of menstrual hygiene management in high schools in Magelang.Methods: This research was conducted in 5 public high schools in Magelang. This research method is a mixed methods design. explanatory The research was conducted by collecting quantitative data then qualitative data. The study population was all high school students in Magelang City with a total of 267 respondents.Results: The results showed that there was a relationship between the peer support variable (p-value 0,000), the role of the teacher (p-value 0.002), and facilities (p-value 0.003) with menstrual health management practicesConclusion: conclusions and implications for midwifery and nursing practiceAll sections in The peer support variable (p value 0.001) had the most influence on menstrual hygiene management. It is hoped that midwives can contribute in providing health education on Menstrual Hygiene Management (MKM) in cross-sectoral collaboration with the Education Office